Pendampingan Pengembangan Project Ethno-Worksheet Bagi Guru SD 4 Dersalam - Ulya, Himmatul; Ardianti, Sekar Dwi (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
The purpose of this service activity is to provide knowledge to SD 4 Dersalam teachers regarding the development of an ethno-worksheet project for SD 4 Dersalam teachers. The method used in this service is to provide interactive training and mentoring. Furthermore, in the training process, there is a two-way interaction so as to provide opportunities for SD 4 Dersalam teachers as training participants to contribute ideas, opinions, thoughts, and experiences. The implementation of ethno-worksheet project development assistance for SD 4 Dersalam teachers is designed in several stages, including planning, implementation, follow-up, simulation, and evaluation. The result of this service activity was that teachers at SD 4 Dersalam Kudus were able to develop ethno-worksheet projects, especially on mathematics and science content based on Kudus local excellence which could help activate students in learning activities.